Redeeming the maverick - Rimmer, Christine (Montana mavericks., 2024)
Hayes Parker swore he would never return to Tenacity, a town that had given him nothing but hard feelings and heartbreak. Now his father's illness has beckoned him home to the family ranch, bringing him face-to-face with...her. Chrissy Hastings, the one who got away. Hayes has changed a lot since he was a hotheaded teen. But he can't just pick up where they left off. First, he must prove he's a man she can count on...for keeps.